3p + 7 = 9 + 8p
3p + 7 - 3p = 9 + 8p - 3p
7 = 9 + 5p
7 - 9 = 9 + 5p - 9
- 2 = 5p
- 2/ 5 = 5p/5
- 2/5 = p
The answer is p = - 2/5
Insert the p value into the equation
- - - - - - - - - - - - - - - - - - - - - - -
Check
3p + 7 = 9 + 8p
3(- 2/5) + 7 = 9 + 8(- 2/5)
- 6/5 + 7 = 9 + (- 16/5)
- 1.2 + 7 = 9 + (- 3.2)
5.8 = 9 - 3.2
5.8 = 5.8
- - - - - - -s-
2006-11-04 07:06:29
·
answer #1
·
answered by SAMUEL D 7
·
0⤊
0⤋
Solution:
3p +7=9+8p
3p-8p=9-7
-5p=2
p= -2/5 ans.
2006-11-04 14:01:45
·
answer #2
·
answered by msb0pk 1
·
1⤊
0⤋
2 over 5
2006-11-04 15:05:07
·
answer #3
·
answered by tinkerbell 4
·
0⤊
0⤋
3p + 7 = 9 + 8p
subtract 3p from both sides
7 = 9 + 5p
subtract 9 from both sides
-2 = 5p
divide both sides by 5
-2/5 = p
---- or ---
p = -2/5 ----in decimal --- p = -0.40
2006-11-04 13:57:58
·
answer #4
·
answered by Bob 5
·
1⤊
0⤋
3p+7=9+8p subtract 8p -7 from each side
-5p=2 divide by -5
p=-.4
2006-11-04 14:47:17
·
answer #5
·
answered by yupchagee 7
·
0⤊
1⤋
(put the ps on one side) 3p-8p=9-7
(calculate it) -5p=2
(divide both sides by -5) p = -2/5
2006-11-04 13:53:56
·
answer #6
·
answered by nax 2
·
1⤊
0⤋
p= -2/5
2006-11-04 13:56:56
·
answer #7
·
answered by SG 5
·
1⤊
0⤋
3p+7=9+8p
5p=-2
p=-2/5
2006-11-04 14:04:31
·
answer #8
·
answered by openpsychy 6
·
1⤊
0⤋
3p - 8p = 9 - 7
5p = -2
p= - 2/5
2006-11-04 14:43:43
·
answer #9
·
answered by Anonymous
·
1⤊
0⤋
-2/5
2006-11-05 00:19:59
·
answer #10
·
answered by live&learn 2
·
0⤊
0⤋